Addition of Sm0.2Ce0.8O1.9 Carbonate into Perovskite Cathode Materials for Low-Temperature Solid Oxide Fuel cell: Short Review - Tan, Kang Huai; Hamimah, Abd Rahman; Muhammad Izzat Nor, Ma'arof (INTI International University, 2022)
Solid Oxide Fuel Cells (SOFCs) are considered one of the most efficient energy conversion devices to meet sustainable and environmental energy resources. The high operating temperature (>800oC) of SOFCs restrains the fabrication cost, material selection, and long-term material durability. Therefore, those cons of HT-SOFC have initiated the efforts of lowering down the SOFCs operating temperature. This article extensively reviews the materials development in low-temperature solid oxide fuel cells (LT-SOFC) (<600oC). Sm0.2Ce0.8O1.9 carbonate (SDCC) is developed and proved to facilitate ions transportation and low ohmic resistance at low-temperature operation compared to SDC and others electrolyte materials. The composition of carbon and calcination temperature in fabricating SDCC exhibit varying effects on the SDCC characterization and performance. Conventional perovskite materials such as La0.6Sr0.4Co0.2Fe0.8O3-α (LSCF), Ba0.5Sr0.5Co0.8Fe0.2O3-α (BSCF) and Sm0.5Sr0.5Co8O3-α (SSC) are incorporated with SDCC electrolyte materials in the application of the cathode and interconnect coatings as well. The SDCC incorporation in the LSCF perovskite produces excellent power output and low polarization resistance in low temperatures. The incorporation of SDCC into SSC requires further investigation due to the formation of SrCO3 impurity. Besides, BSCF-SDCC perovskite exhibits better material characteristics with no calcination process involved. BSCF-SDCC attains low area-specific resistance.